2015
DOI: 10.1007/s12015-014-9582-4
|View full text |Cite
|
Sign up to set email alerts
|

Gene and MicroRNA Profiling of Human Induced Pluripotent Stem Cell-Derived Endothelial Cells

Abstract: hiPSC-ECs and hESC-ECs exhibited a high degree of similarity with HUVECs in EC-associated genes expression. And the miRNA profiling analysis revealed significant differences between hiPSCs and hESCs, but a high degree of similarity between hiPSC-ECs and hESC-ECs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 35 publications
0
14
0
1
Order By: Relevance
“…In addition, vascular invasion is an important step in metastasis to distant sites, and angiogenesis and its regulators are associated with tumor growth and prognosis in various solid tumors, including lung cancer [42, 43]. In this context, miR-27b-3p is a pro-angiogenic microRNA [40, 44] that is up-regulated in vascular endothelial cells [4547]. In a recent mouse study, increased miR-27b-3p expression resulted in enhanced neovascularization and contributed to tumor growth [44].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, vascular invasion is an important step in metastasis to distant sites, and angiogenesis and its regulators are associated with tumor growth and prognosis in various solid tumors, including lung cancer [42, 43]. In this context, miR-27b-3p is a pro-angiogenic microRNA [40, 44] that is up-regulated in vascular endothelial cells [4547]. In a recent mouse study, increased miR-27b-3p expression resulted in enhanced neovascularization and contributed to tumor growth [44].…”
Section: Discussionmentioning
confidence: 99%
“…Yoo et al, [88] reported two novel miRs, miR-6086 and miR-6087, which target vascular endothelial (VE-)cadherin and endoglin, respectively, and their expression is down regulated during EC differentiation [88]. Another study demonstrated that the expression of miR-99b, miR-181a, and miR-181b was increased in ECs during differentiation [89], which was reconfirmed by another group recently [90]. Interestingly, although over expression of these miRs promotes EC differentiation, their knockdown has no significant impact on EC differentiation of hESCs [89].…”
Section: Esc Specific Mirs Regulating Their Commitment To Ecsmentioning
confidence: 73%
“…Recently, Chen and colleagues identified miR-199a and miR-199b as differentially regulated miRs during EC differentiation [109] [110] but their role in EC differentiation needs to be verified. Likewise, Wang et al, [90] have performed an extensive miR profiling of hiPSCs and differentiated ECs and identified several differentially regulated miRs including miR-20a, miR-20b, miR-27b, miR-100, miR-125a-5p, miR-137, miR-149, miR-181a, miR-210, miR-222, and miR-296-5p, however, their role in EC differentiation of iPSCs is not verified yet.…”
Section: Induced Pluripotent Sc-specific Mirsmentioning
confidence: 99%
“…Generation of endothelial cells from pluripotent stem cells of various origins has been reported and is now well established . Characterization of the generated endothelial cells, including gene expression pattern, has revealed significant information regarding overall expression profile of endothelial specific genes . These studies have also lead to significant insights into the vascular bed/organ‐specific characteristics of endothelial cells, as well as contributions of signaling pathways, epigenetics regulators, secreted molecules, and membrane bound cell surface receptors in regulation of endothelial‐specific gene expression .…”
Section: Introductionmentioning
confidence: 99%